2010
DOI: 10.5539/ijbm.v5n10p234
|View full text |Cite
|
Sign up to set email alerts
|

Developing and Testing a Model of Burnout at Work and Turnover Intensions among Doctors in Pakistan

Abstract: This paper examines the impact of burnout at work (BO), work life balance (WLB), work life conflict (WLC) and job satisfaction (JS) on turnover intensions (TOI) among doctors in Pakistan. The research team developed a conceptual model to test the hypothesized relationships between the variables. Simple random sampling method was used to distribute 300 questionnaires among MBBS qualified doctors working in the private and public sector hospitals in major cities of Pakistan, such as Peshawar, Lahore, Rawalpindi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 58 publications
1
4
0
1
Order By: Relevance
“…The first hypothesis that a positive relationship between WFC and turnover intentions among married female doctors would be found -was upheld. Findings of previous empirical studies 22,26 are also consistent with the present study's findings. Both work interference with family and family interference with work domains were positively related to turnover intentions in this study reflecting a dilemma that married working women face.…”
Section: Discussionsupporting
confidence: 93%
“…The first hypothesis that a positive relationship between WFC and turnover intentions among married female doctors would be found -was upheld. Findings of previous empirical studies 22,26 are also consistent with the present study's findings. Both work interference with family and family interference with work domains were positively related to turnover intentions in this study reflecting a dilemma that married working women face.…”
Section: Discussionsupporting
confidence: 93%
“…Generally, healthy work-life balance is an important issue in workplace because as mentioned earlier it can potentially influence employee"s well-being and attitudes towards their company [30] and cause other outcomes such as increased productivity, loyalty, decreased turnover intention and actual turnover [10][11][12][13]31].…”
Section: Work-life Balancementioning
confidence: 99%
“…The proposed model suggests that work intensification is negatively related to work-life balance [7,44] but is positively related to turnover intention [8,9,45]. On the other hand, positive work-life balance will lower turnover intention [10,31]. It is also likely that work intensification will have indirect effects via work-life balance to help reduce turnover intention of academics.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Voluntary turnover behaviour takes place in form of discretionary actions carried out by employees in form of deliberate staff resignations, prolonged or extra leave requests, absconding from duty, unexplained and prolonged absenteeism, and failed return-to-work discussions (Imran-Malik, Zaheer, Mehboob & Khan, 2010;Lambert & Hogan 2008;According to Zeynep and Huckman, 2008). Voluntary turnover behaviour is also reflected by its consequences such as incurring of unexpected staff replacement costs, extra workloads to the remaining staff members, overtime payments, missed deadlines, interruptions to the flow of work, higher levels of stress-related absence, low staff morale, declining staff productivity, and unsatisfactory services to customers (Shaw, 2010;Zeynep & Huckman, 2008).…”
Section: Staff Turnover Behaviourmentioning
confidence: 99%
“…The intentions are expressed in form of buying and/or reading newspapers to find advertised jobs, making job applications to other organizations when still holding the current job, and making online and other enquiries about whether there are vacant posts in other organizations (Kyomuhendo, 2012). It has been observed that employees develop intentions to stay or leave an organization basing on various reasons ranging from personal reasons to those related to how they are treated by their organizations (Imran-Malik et al, 2010). This paper focuses on how organizations, particularly universities in Uganda, treat their academic employees in terms of professional empowerment.…”
Section: Staff Turnover Behaviourmentioning
confidence: 99%